Energieversorgungsrisiken, Energiepreiskrise und Klimaschutz erfordern gemeinsame Antworten; Energy supply risks, the energy price crisis and climate protection require joint responses - Manfred Fischedick (Wirtschaftsdienst, 2022)
– In the past two years, the world has changed and global crises (e. g. the COVID-19 pandemic, war in Ukraine) increasingly dominate the headline. Decades of certainties no longer apply, risks and uncertainties are increasing, challenges are becoming more complex and at the same time require faster and more consistent action. Against that background, the text discusses what we can - and must - learn from the current crises. We must learn that we need to be more sensitive to potential risks and take precautions where necessary and possible, even if this requires pre-emptive financial and structural actions. The text focuses onis the current situation in which we have to find integrative answers reflecting the severe energy supply risks (associated with the energy import dependency from Russia) and the rising and volatile energy prices on the one hand and the climate protection challenge on the other.
Keywords: P18; Q42; Q48; 330; Energieversorgung; Energiepreis; Klimaschutz